Direct Photo-Thermal Energy Storage Using Nanoparticles Laden Phase Change Materials - Moudgil, Deepak (My University, 2019)
Thermal energy storage provides an efficient means of storing energy (during peak production period) and utilizing the stored energy during the peak load duration (particularly for heating and cooling household/industrial requirements). In other words, thermal storage ensures clean and uninterrupted energy supply at minimal additional operating costs. Storing solar energy is a clean and advantageous proposition. In this realm, we propose that seeding nanoparticles into pristine paraffin wax (due to their improved thermo-physical optical characteristics) could significantly enhance the charging rate and thus the thermal energy produce. In the present work, we have performed experiments to predict the charging rates when paraffin wax/nanoparticles dispersion directly (volumetrically) interacts with the sunlight. Broad absorption-based nanoparticles (amorphous carbon) have been seeded into the pristine phase change material (paraffin wax) to enhance photo-thermal conversion efficiency. In order to clearly identify the effects of adding nanoparticles, two systems of top heating have been studied (i.e. the one with surface heating and the other volumetric heating with nanoparticles dispersed in paraffin wax) and two systems of bottom heating have been studied (i.e. the one with surface heating and the other volumetric heating with nanoparticles dispersed in paraffin wax) under similar operating conditions. To understand the role of nanoparticles; samples of pristine paraffin wax and nano-PCMs (i.e. different concentrations of NPs) have been optically heated. Furthermore, optical charging has been compared with the conventional thermal charging process. As per experimental results, the optical charging scheme significantly improves the thermal charging rate (by more than 157% during top heating) at optimum nanoparticle concentration (0.2%, in the present study), in the same way the optical charging scheme significantly improves the thermal charging rate (by more than 81% during bottom heating) at optimum nanoparticle concentration (0.2%, in the present study) as compared to conventional thermal charging. The temperature distribution and thermal profile measurements of the Nano-PCMs collected through aforesaid process reveals that optical heating of PCM in presence of nanoparticles could definitely prove to be an improved method of charging.
Keywords: optical charging; phase change material (PCM); nanoparticles